Large artery stiffness and pulse wave reflection: results of a population-based study - Filipovský, Jan; Tichá, Milena; Cífková, Renata; Lánská, Vera; Stastná, Vlasta; Roucka, Patrik (Blood pressure, 2005)
OBJECTIVE: To assess the determination of large artery stiffness and pulse wave reflection in a population sample. METHODS: A 1% random population sample aged 25-65 years was selected in nine districts of the Czech Republic for a survey off cardiovascular risk factors (Czech post-MONICA). Of 891 individual screened in the Pilsen centre in the year 2000, arterial properties were studied in 291 (143 males and 148 females) using the Sphygmocor device. Pulse wave velocity (PWV) in the aorta and in the lowe limbs was measured to assess large artery stiffness. Wave reflection was assessed from radial pulse wave analysis; the main estimated parameter was peripheral augmentation index (PAI) defined as P2/P1 = ratio of pulse pressures measures at the peaks of secondary and primary waves. RESULTS: Aortic PWV increased with age (p < 0.001) and was similar in both sexes. Lower extremity PWV increased with age in women, but not in mean, and its mean value was higher in men (p < 0.001). PAI was higher in females in all age groups (p < 0.001) and increased steeply with age in both sexes (p < 0.001). PAI was increased in current smokers (p < 0.001 in both sexes) and in male smokers, the reflected wave returned earlier than in male non-smokers (p < 0.05). Correlation coefficient of PAI with aortic PWV was 0.22 (p < 0.01), and with central augmentation index (CAI), derived from PAI by mathematical transformation, was 0.94 (p < 0.001). Multiple regression analyses, where age, sex, systolic blood pressure (SBP), total cholesterol level, smoking, glucose level and body mass index were included as independent variables, were performed. PAI was better predicted than aortic or lower extremity PWV is these models (41%, 14% and 10% of variance explained, respectively). Age, female sex, smoking, SBP and total cholesterol predicted PAI level whereas age, SBP and glucose level were the main determinants pf aortic PWV. CONCLUSION: Of the studied arterial parameters, PAI showed the closest association with cardiovascular risk factors. The correlation between PAI and aortic PWV was loose, and both parameters had practically different determinants. PAI, which is obtained by direct measurement above radial artery, was practically identical with the mathematically derived CAI in the studied population sample, and therefore, it is a suitable parameter for studying the phenomenon of wave reflection.
Keywords: Regression Analysis; dospělí; Female; Adult; ženské pohlaví; arteria radialis; aorta; lidé; pulz; Vascular Resistance; regresní analýza; cévní rezistence; Risk Factors; Sex Factors; Arteries; Male; Pulsatile Flow; Cardiovascular Diseases; Aged; sexuální faktory; Czech Republic; Radial Artery; diagnostické techniky kardiovaskulární; Blood Pressure Determination; rizikové faktory; kardiovaskulární nemoci; Česká republika; měření krevního tlaku; lidé středního věku; Aorta; senioři; mužské pohlaví; pulzatilní průtok; Diagnostic Techniques, Cardiovascular; Pulse; Middle Aged; arterie; Humans